2010
DOI: 10.1021/am100593b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Uniform-Size Hollow Silica Microspheres through Interfacial Polymerization in Monodisperse Water-in-Oil Droplets

Abstract: We have developed a microfluidic method to produce monodisperse, size-controllable silica microspheres via hydrolysis and polymerization of TEOS at the interface of water-in-oil droplets. By altering the concentration of TEOS in oil phase and CTAB in aqueous phase, we achieved control over morphology of the microspheres from hollow, to partly hollow, to solid. The hollow silica microsphere can be used for rapid waste removal and detoxification extraction with a very simple procedure.National Scientific Foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 32 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…Up to now, various synthetic techniques such as spray drying [14,20], interfacial polymerization [21,22], self-assembly [5,11], layer-by-layer (LBL) fabrication [23,24], and templating have been established for making hollow silica particles. Among these methods, the templating method is popular, which uses polymeric spheres [8][9][10][25][26][27], micelles [6,28], droplets [7,[29][30][31], and inorganic particles [3,16,19] as templates.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various synthetic techniques such as spray drying [14,20], interfacial polymerization [21,22], self-assembly [5,11], layer-by-layer (LBL) fabrication [23,24], and templating have been established for making hollow silica particles. Among these methods, the templating method is popular, which uses polymeric spheres [8][9][10][25][26][27], micelles [6,28], droplets [7,[29][30][31], and inorganic particles [3,16,19] as templates.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, reaction condition control for particle nucleation and growth from RTD, reactant concentration, or temperature in the microreactors is also important 37b,104. By carefully designing the component, concentration and temperature, complex particle structures, including hollow, rod, donut, and raspberry, can also be made. In different kinds of oxide materials, magnetic nanoparticles keep attracting researchers in recent years.…”
Section: Applications Of Flow Chemistry Technologies For Different Namentioning
confidence: 99%
“…TEM images of hollow mesoporous silica nano/microspheres prepared via hard-templating route: A) P4VP were used as templates. [35] Copyright 2010, American Chemical Society. [30] Copyright 2011, American Chemical Society.…”
Section: Hollow Silica Nano/microspheres Versus Silica-coated Pe Micrmentioning
confidence: 99%
“…[34] Chang et al [27] have shown a high perspective of w/o microemulsion method in synthesis of enzyme-encapsulated hollow silica particles. [35] The dispersed aqueous phase containing ammonia and CTAB was slowly injected into the inlet of the cross-flow microfluidic device in order to fabricate uniform water-oil droplets which further interact with TEOS forming silica microspheres. After the TEOS and aqueous solution were introduced, the w/o mixture was stirred for 8 h at 20 °C to form enzyme-incorporated silica nanoparticles.…”
Section: Hollow Silica Nano/microspheres Versus Silica-coated Pe Micrmentioning
confidence: 99%